Do competitively acquired funds induce public research institutions to behave efficiently? - Thomas Bolli; Frank Somogyi (ETH Zurich, KOF Swiss Economic Institute, 2009)
This paper analyzes the effect of public and private third-party funds on the effciency of departments of Swiss public research institutions. Estimating an output distance function assuming that labor is used to produce master students and scientific publications, we find no statistically significant effect of private or public third-party funding on research efficiency. However, once we include technology transfer as an additional output, the coefficient of private funding is statistically significant. We further find that this disciplining effect of private funding is qualitatively robust in a setting controlling for endogeneity.
Keywords: 330; Efficiency; Research; University; Technology Transfer; Third-Party Funding; Public Finance; Hochschulforschung; Wettbewerb; Technologietransfer; Forschungsfinanzierung; Wirtschaftliche Effizienz; Schweiz